2021
DOI: 10.3390/ijms222111936
|View full text |Cite
|
Sign up to set email alerts
|

Tepotinib Inhibits Several Drug Efflux Transporters and Biotransformation Enzymes: The Role in Drug-Drug Interactions and Targeting Cytostatic Resistance In Vitro and Ex Vivo

Abstract: Tepotinib is a novel tyrosine kinase inhibitor recently approved for the treatment of non-small cell lung cancer (NSCLC). In this study, we evaluated the tepotinib’s potential to perpetrate pharmacokinetic drug interactions and modulate multidrug resistance (MDR). Accumulation studies showed that tepotinib potently inhibits ABCB1 and ABCG2 efflux transporters, which was confirmed by molecular docking. In addition, tepotinib inhibited several recombinant cytochrome P450 (CYP) isoforms with varying potency. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…After the lung lobectomy, tumor tissue was immediately excised by the pathologist to collect an NSCLC sample. The isolation of lung cancer cells was based on the method reported in published papers with minor optimizations [18][19][20]. Fragmented pieces 2-5 mm in diameter were separated from the tumor samples using a scalpel.…”
Section: Isolation and Purification Of Nsclc Patient-derived Primary ...mentioning
confidence: 99%
See 3 more Smart Citations
“…After the lung lobectomy, tumor tissue was immediately excised by the pathologist to collect an NSCLC sample. The isolation of lung cancer cells was based on the method reported in published papers with minor optimizations [18][19][20]. Fragmented pieces 2-5 mm in diameter were separated from the tumor samples using a scalpel.…”
Section: Isolation and Purification Of Nsclc Patient-derived Primary ...mentioning
confidence: 99%
“…Cell viability was evaluated based on the MTT assay as described in our previous papers [19,20]. The cells were seeded in 96-well plates at the following densities for a 24-h incubation: MDCKII-par, MDCKII-ABCB1, MDCKII-ABCG2, and MDCKII-ABCC1: 1.5 × 10 4 cells/well; A431-par, A431-ABCB1, A431-ABCG2, and A431-ABCC1: 2.0 × 10 4 cells/well; NCI-H2228: 1.2 × 10 4 cells/well; HCC827: 4.0 × 10 4 cells/well; NSCLC primary culture cells: 1.0 × 10 4 cells/well.…”
Section: Mtt Proliferation Assaymentioning
confidence: 99%
See 2 more Smart Citations
“… 4 The pharmacokinetic interaction of tepotinib with ATP-binding cassette transporters and cytochrome P -450 (CYP) drug-metabolising enzymes as well as their possibility to combat multidrug resistance were explored in vivo and in vitro . 5 Metabolism and in vitro data showed that tepotinib is a substrate of CYP3A4, CYP2C8 and P-glycoprotein (P-gp). However, it is not possible to accurately quantify the fractions metabolised by the individual major CYP isoenzymes.…”
mentioning
confidence: 99%